2023
DOI: 10.1111/acel.13914
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency for scavenger receptors Stabilin‐1 and Stabilin‐2 leads to age‐dependent renal and hepatic depositions of fasciclin domain proteins TGFBI and Periostin in mice

Abstract: Stabilin‐1 (Stab1) and Stabilin‐2 (Stab2) are two major scavenger receptors of liver sinusoidal endothelial cells that mediate removal of diverse molecules from the plasma. Double‐knockout mice (Stab‐DKO) develop impaired kidney function and a decreased lifespan, while single Stabilin deficiency or therapeutic inhibition ameliorates atherosclerosis and Stab1‐inhibition is subject of clinical trials in immuno‐oncology. Although POSTN and TFGBI have recently been described as novel Stabilin ligands, the dynamics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Since TGFBi levels in the liver correlate with fibrosis in all our models and genotypes here, we hypothesize that the TGFBi protein in the liver we observed is not deposited as we previously hypothesized for high TGFBi and POSTN levels in glomeruli and liver tissue from Stab-DKO tissue [ 22 ]. Since no immunofluorescent signal was observed for POSTN, even in strongly fibrotic CDAA-fed livers, we hypothesize that POSTN positivity in Stab-DKO livers is indeed due to deposition from the plasma and fibrogenic stimuli alone are not sufficient to induce strong POSTN depositions as seen in Stab-DKO [ 22 ]. Correlation for POSTN and fibrosis was overall weaker than for TGFBi and fibrosis and did not reach significance in Stab2−/− mice, although TGFBi and POSTN levels correlated well overall, which is in line with previous findings [ 22 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Since TGFBi levels in the liver correlate with fibrosis in all our models and genotypes here, we hypothesize that the TGFBi protein in the liver we observed is not deposited as we previously hypothesized for high TGFBi and POSTN levels in glomeruli and liver tissue from Stab-DKO tissue [ 22 ]. Since no immunofluorescent signal was observed for POSTN, even in strongly fibrotic CDAA-fed livers, we hypothesize that POSTN positivity in Stab-DKO livers is indeed due to deposition from the plasma and fibrogenic stimuli alone are not sufficient to induce strong POSTN depositions as seen in Stab-DKO [ 22 ]. Correlation for POSTN and fibrosis was overall weaker than for TGFBi and fibrosis and did not reach significance in Stab2−/− mice, although TGFBi and POSTN levels correlated well overall, which is in line with previous findings [ 22 ].…”
Section: Discussionmentioning
confidence: 62%
“…Since our previous studies have shown that Stab1 and Stab2 can compensate each other to a certain degree, regarding scavenging of ligands like POSTN and TGFBi [ 8 , 22 ], we tested whether a pro-fibrotic stimulus adding on single Stabilin deficiency might trigger pronounced liver fibrosis and ligand deposition comparable to Stabilin-double-deficient mice. Interestingly, only a moderate pro-fibrotic stimulus with a MCD diet for two weeks showed differences between genotypes regarding overall fibrosis, which strongly mirrored baseline changes in fibrotic burden observed in each genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFBI plays a key role in the activation of PI3K/AKT/mTOR/ HIF-1α signaling pathway in RCC Previous literature has reported a close relationship between POSTN and TGFBI [19][20][21][22], We analyzed the correlation between TGFBI and POSTN at RNA, total protein, and phosphoprotein levels and found a positive correlation between the expression of the two (Fig. 6A), whereas previous studies have been performed on POSTN indicating the importance of the AKT/mTOR pathway in RCC [23] .…”
Section: Tgfbi Knockdown Inhibits Expression Of Epithelial-mesenchyma...mentioning
confidence: 99%
“…KO models of stabilin-1 or -2 showed decreased atherosclerotic plaque formation under Western diet conditions or ApoE KO 38 , 39 —the effect was replicated using monoclonal antibodies and suggested as a therapy against atherosclerosis in prone individuals, as antibodies would likely not greatly interfere with liver endothelial scavenging 39 . Stabilin double KOs exhibit transforming growth factor beta induced protein (TGFBI) and Periostin (POSTN) deposition in liver and in glomeruli with age 40 . Even single KO models were found to have increased inappropriate deposition of connective tissue components, and showed more severe steatosis and fibrosis in induced models 41 .…”
Section: Introductionmentioning
confidence: 99%